A Conceptual Review to Approach Traditional Homegardens as Fields of Social Practice - Lope-Alzina, Diana Gabriela (Ethnobiology and Conservation, 2017)
Disciplines and approaches concerned with peopleenvironment relations have contributed to legitimate traditional ecological knowledge, nowadays endorsed in the international scientificpolicy agenda as an important driver for management and conservation of biological resources. However, there is still a need to further understand how people internalize worldviews, knowledge, and practices regarding environmental management. In this sense, traditional homegardens are a suitable scenery to unravel such processes. Grounded on Bourdieu´s´theory of practice´, this paper unveils homegardens as fields of social practice. The homegarden field is embedded within the household field, further influenced by the community field. The three of them make up the ‘array of fields’ where homegardening develops by means of social interactions, informing and informed by the habitus (schemes of perception, appreciation, and action, produced by particular social environments that shape agent’s own sense of the world and his/her place in it). Both, inputs (e.g. land, plants, labor, and knowledge) and outputs (e.g. increased knowledge, homegarden produce, homegarden functions and derived benefits) are here approached as homegarden´s capitals. According to the theory of practice, such capitals are unequally distributed across agents, and it is such inequality that impulses them to generate, maintain, increase and/or transform homegarden capitals.